Dental management of a child with a rare bone disorder: a case report with a six-year follow up - Suélen Alves TEIXEIRA; Mariana Oliveira GUIMARÃES; Natália Mendes De Matos CARDOSO; Raiane Machado MAIA; Natália Cristina Ruy CARNEIRO; Ana Cristina BORGES-OLIVEIRA (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Osteogenesis imperfecta is a rare genetic disorder involving abnormal type I collagen composition that compromises bone and collagen-rich tissues. Individuals with Osteogenesis imperfecta exhibit oral and systemic abnormalities, including dentinogenesis imperfect. The purpose of the review is to report a clinical case of a nine-year-old boy diagnosed with Osteogenesis Imperfecta type III, focusing on dental and occlusal aspects. The case report was developed at the outpatient clinic at the School of Dentistry of the Federal University of Minas Gerais, in Southeastern of Brazil. The clinical oral examination revealed Angle Class III malocclusion and anterior crossbite. It was also observed the presence of dentinogenesis imperfect in both primary and permanent teeth. Radiographic analysis showed the presence of completed obliterated pulp chambers in both dentitions. Dental treatment included oral hygiene counseling, dental extraction, fluoride therapy and restorations. The child was followed up for a period of six years and then referred to the orthodontic outpatient clinic at the same university for the treatment of malocclusion. Early dental care is important to the prevention or interception of oral diseases, such as dentinogenesis imperfect and malocclusion, as well as the improvement of dental esthetics in cases of Osteogenesis Imperfecta.